THE SOCIAL MOVEMENT OF ATENCO: EXPERIENCE AND MAKING SENSE (Andamios, Revista de Investigación Social, 2010)
In October 2001, the federal government issued nineteen expropriating decrees in order to build a new airport in Texcoco, Estado de México. Against this decision, a group of peasants (“ejidatarios”) and dwellers from several communities set up the social movement of Atenco. In this paper, we will analyze the interpretative dimension of the atenquense struggle, and the relevance of the experience in the constitutive process of this collective actor. In order to achieve this objective, we will consider some theoretical coordinates from the marxist historian E. P. Thompson, Barrington Moore and the framing theory.
Keywords: Social movement; collective action; experience; grievance; framing process